Edge-chipping reduction in rotary ultrasonic machining of ceramics: finite element analysis and experimental verification - Li, Z. C.; Cai, Liang-Wu; Pei, Zhijian J.; Treadwell, C. (My University, 2006)
Rotary ultrasonic machining (RUM) is one of the machining processes for advanced ceramics. Edge chipping (or chamfer), commonly observed in RUM of ceramic materials, not only compromises geometric accuracy but also possibly causes an increase in machining cost. In this paper, a three-dimensional finite element analysis (FEA) model is developed to study the effects of three parameters (cutting depth, support length, and pretightening load) on the maximum normal stress and von Mises stress in the region where the edge chipping initiates. Two failure criteria (the maximum normal stress criterion and von Mises stress criterion) were used to predict the relation between the edge chipping thickness and the support length. Furthermore, a solution to reduce the edge chipping is proposed based upon the FEA simulations and verified by experiments.
Keywords: Ceramic; Edge chipping; Finite element analysis; Grinding; Machining; Rotary ultrasonic machining